Digitalisasi Pembelajaran Tahfidz Al-Qur'an Berbasis AI Dalam Inovasi Tantangan Dan Implementasi - Lutfi Azzahrowaini; Muhammad Wildan Shohib; Muhammad Nur Rochim Maksum (Universitas Hamzanwadi, 2025)
The implementation of Artificial Intelligence (AI) in the digitalization of Tahfidz Al-Qur'an learning management has brought significant improvements in enhancing the effectiveness and efficiency of the memorization process. AI technology enables personalized learning and real-time monitoring of students' memorization progress through features such as Automatic Speech Recognition (ASR), data-driven muraja’ah systems, and adaptive feedback. However, the implementation of AI faces major challenges, including infrastructure limitations, teacher readiness, and the need to uphold ethical standards and student data privacy in accordance with Maqasid Syariah principles. This study aims to explore the effectiveness of AI implementation in Tahfidz Al-Qur'an, identify its primary benefits, and formulate optimal strategies for adopting AI in Islamic educational institutions. The findings indicate that the combination of traditional talaqqi methods with AI technology can create a more adaptive and innovative learning system while preserving Islamic educational values.